Ambientes virtuais de aprendizagem colaborativa – uma ferramenta para formação humana integral: estudo de caso no IFAP - Brito, Maria de Fátima dos Santos (2019)
The research is developed in the Professional Master's Program in Professional and Technologi cal Education in National Network (ProfEPT) Polo do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas (IFAM) Campus Manaus with the objective of developing a proposal to use the tools of the Virtual Learning Environment (AVA) in a perspecti ve of integral human formation (EaD) at Instituto Federal de Educação, Ciência e Tecnologia do Amapá (IFAP) Campus Macapá. As a methodology, the study has a qualitative approach of an applied and descriptive nature, having as a methodological procedure t he case study. In order to reach the objective of this investigation, a methodological path was traced that began with a bibliographical theories research that guided the construction of the theoretical reference. After that, an exploration of the resource s and activities available on the institution's platform was carried out, followed by a field research with teachers and students of the course under study, in order to collect information regarding the research problem, besides providing subsidies for the construction of the educational product. As the main result, teachers and students have demonstrated difficulties in relation to AVA tools, limiting to the use of few MOODLE resources. Based on the results, we proceeded with the construction of the educat ional product that had the elaboration and evaluation stages, the latter having a positive result regarding the agreement parameter and some suggestions for improvemen t. Thus, necessary adjustments were made, finalizing the educational product development stages with the conclusion and production of the “MOODLE User Guide for Integral Human Training”, which aims to guide teachers on the use and functionality of the resources available on the MOODLE platform. IFAP, so that it signals a perspective of integral human formation.